Penerapan Perilaku Hidup Sehat Untuk Meminimalisir Angka Stunting di Desa Gadungan - Zuraidah Zuraidah; Ni’matur Rohmah; Aulia Putri Siti Aminah (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2022)
Community service activities are carried out in the form of stunting socialization in Gadungan village with the aim of minimizing the high stunting rate in the community. The method used is Participatory Action Research (PAR) using a qualitative approach. from the data obtained by the Gadungan village community who experienced stunting as many as 114 toddlers under the age of 5 years. Factors that cause high stunting rates are the lack of assistance in child nutrition and an unhealthy lifestyle. besides that, it is also caused by marriage at an age that is not ideal so that there is no mental readiness in marriage. Keywords: socialization, stunting, healthy lifestyles